The ubiquitin E3 ligase TRAF6 exacerbates pathological cardiac hypertrophy via TAK1-dependent signalling - Ji, Yan-Xiao (Nat Commun, 2016)
Tumour necrosis factor receptor-associated factor 6 (TRAF6) is a ubiquitin E3 ligase that regulates important biological processes. However, the role of TRAF6 in cardiac hypertrophy remains unknown. Here, we show that TRAF6 levels are increased in human and murine hypertrophied hearts, which is regulated by reactive oxygen species (ROS) production. Cardiac-specific Traf6 overexpression exacerbates cardiac hypertrophy in response to pressure overload or angiotensin II (Ang II) challenge, whereas Traf6 deficiency causes an alleviated hypertrophic phenotype in mice. Mechanistically, we show that ROS, generated during hypertrophic progression, triggers TRAF6 auto-ubiquitination that facilitates recruitment of TAB2 and its binding to transforming growth factor beta-activated kinase 1 (TAK1), which, in turn, enables the direct TRAF6–TAK1 interaction and promotes TAK1 ubiquitination. The binding of TRAF6 to TAK1 and the induction of TAK1 ubiquitination and activation are indispensable for TRAF6-regulated cardiac remodelling. Taken together, we define TRAF6 as an essential molecular switch leading to cardiac hypertrophy in a TAK1-dependent manner.